2001
DOI: 10.2519/jospt.2001.31.12.730
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Joint Position on Electromyographic and Torque Generation During Maximal Voluntary Isometric Contractions of the Hamstrings and Gluteus Maximus Muscles

Abstract: Study Design: Repeated measures analysis o i joint angle e i i~t s on hip and k n w muscle cltrtromyographic IEMGI activitv. Objectives: To simultan~~usly determine angle-dependent changes in maximal voluntary isometric contraction IMVICI torque and EMG activity during hip extension and knee ilexion. Background: Procedures ior normalizing EMG data and ior determining torque-angle relationships for various joint motions both entail asking suhjects to exert an MVIC. The implicit assumption in t h r w paradigms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 19 publications
8
108
3
1
Order By: Relevance
“…All test positions were based on those identified in the literature and were gravity resisted. [20][21][22][23][24] We chose the test position (30° knee flexion) for knee-extension strength used by Walsworth et al 23 because we felt that this position better tests the ability of subjects to generate force at a knee-flexion angle they would experience during single-leg jumps. Straps were used to stabilize the subject and handheld dynamometer (Lafayette Instruments, Lafayette, IN) to eliminate the influence of tester strength on these measurements.…”
Section: Methodsmentioning
confidence: 99%
“…All test positions were based on those identified in the literature and were gravity resisted. [20][21][22][23][24] We chose the test position (30° knee flexion) for knee-extension strength used by Walsworth et al 23 because we felt that this position better tests the ability of subjects to generate force at a knee-flexion angle they would experience during single-leg jumps. Straps were used to stabilize the subject and handheld dynamometer (Lafayette Instruments, Lafayette, IN) to eliminate the influence of tester strength on these measurements.…”
Section: Methodsmentioning
confidence: 99%
“…This highest activity level was probably due to the fact that, during these exercises, the hamstrings were in active insufficiency and their capacity to produce or maintain active tension was diminished. Worrell et al 19 observed increases in gluteus maximus activity during exercises performed with KF at 30° and 60° when compared to 90°. In the present study, the peak activity of the gluteus maximus occurred close to the end of the movement.…”
Section: Discussionmentioning
confidence: 97%
“…MVIC measurements of the gluteus maximus were carried out with the hip in maximum extension and with 90° of knee flexion for the semitendinosus muscle. Worrell et al 19 recommended that the normalizing contractions should be performed at joint angles close to that assumed during the activity of interest. During the MVIC measures, verbal encouragements were given to the participants to reach maximal muscular activation.…”
Section: Methodsmentioning
confidence: 99%
“…To record muscle activity, Surface electrodes (Ag/AgCl) were placed parallel to the muscle fibers [18]. Electrodes placement to collect EMG signals were as follow: for UT at the midpoint of a line running between the C7 spinous process and the lateral tip of the acromion [19] and for the GM, at the mid point of a line running from S2 to the greater trochanter [20]. The reference electrode was placed over the right ulnar styloid process.…”
Section: Instrumentations For Assessmentmentioning
confidence: 99%
“…The first leg to be assessed was chosen by cards and the patient chose the card randomly, the word written in the card was (right side first or lift side first). The positions of limb and foot were manually and verbally supervised throughout the performance to ensure that the subject maintained neutral hip rotation, full knee extension, and neutral ankle flexion, because outward rotation of the hip joint and ankle dorsiflexion especially facilitated the glutei [20]. Before testing, the participants were familiarized with the standard position and movement.…”
Section: Instrumentations For Assessmentmentioning
confidence: 99%